Implementasi Metode Artificial Neural Network (ANN) Model Based On Use Case Point Dalam Menghitung Biaya Perangkat Lunak (Studi Kasus CV. Profile Image Studio) - Ade Pratama; Andi Reza Perdanakusuma; Djoko Pramono (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Software cost estimation is an important part of an information technology project for budgeting. In the process of determining the price of a system CV. The Profile Image Studio does not use the scientific standard format or is commonly called parametric, they only use the guesstimate method. It is only estimates based on intuition. Based on this case, the cost estimation in this study will implement Artificial Neural Network (ANN) model Based on Use Case Point method is implemented in calculating software costs as suggestion for CV. Profile Image Studio. Cost estimates can be obtained after obtaining estimated effort, number of human resources and estimated system development time. Artificial Neural Networks (ANN) Based on Use Case Point method is implemented in 2 systems that have been developed by CV. Studio Profile Image. At the end of this study, the cost comparison of system development was done by comparing estimated cost results obtained using the Artificial Neural Network (ANN) model based on the Use Case Point with the allocation of costs incurred by CV. Studio Profile Image. The results of applying the Artificial Neural Network (ANN) model Based on the Use Case Point method in calculating software costs, it was found that the total estimated cost of the DBA ticket system was Rp. 17,703,140 carried out by 12 people in 1247.46 hours while the pintu air system was Rp. 6,436,860 carried out by 12 people in 453.6 hours.